Dynamics in the outskirts of four Milky Way globular clusters: it's the tides that dominate. Issue 1 (8th December 2022) - Wan, Zhen; Arnold, Anthony D; Oliver, William H; Lewis, Geraint F; Baumgardt, Holger; Gieles, Mark; Hénault-Brunet, Vincent; de Boer, Thomas; Balbinot, Eduardo; Da Costa, Gary; Mackey, Dougal; Erkal, Denis; et al.
ABSTRACT: We present the results of a spectroscopic survey of the outskirts of four globular – 1261, NGC 4590, NGC 1904, and NGC 1851 – covering targets within 1° from the cluster centres, with 2dF/AAOmega on the Anglo-Australian Telescope (AAT) and FLAMES on the very large telescope (VLT). We extracted chemo-dynamical information for individual stars, from which we estimated the velocity dispersion profile and the rotation of each cluster. The observations are compared to direct N -body simulations and appropriate limepy /spes models for each cluster to interpret the results. In NGC 1851, the detected internal rotation agrees with existing literature, and NGC  1261 shows some rotation signal beyond the truncation radius, likely coming from the escaped stars. We find that the dispersion profiles for both the observations and the simulations for NGC 1261, NGC 1851, and NGC 1904 do not decrease as the limepy /spes models predict beyond the truncation radius, where the N -body simulations show that escaped stars dominate; the dispersion profile of NGC 4590 follows the predictions of the limepy /spes models, though the data do not effectively extend beyond the truncation radius. The increasing/flat dispersion profiles in the outskirts of NGC 1261, NGC 1851, and NGC 1904, are reproduced by the simulations. Hence, the increasing/flat dispersion profiles of the clusters in question can be explained by the tidal interaction with the galaxy without introducing dark matter.